2022
DOI: 10.1186/s12903-022-02122-4
|View full text |Cite
|
Sign up to set email alerts
|

Deleterious oral habits related to vertical, transverse and sagittal dental malocclusion in pediatric patients

Abstract: Background Malocclusion is highly reported among mixed dentition cases. Therefore, we aimed to determine the relationship of dental malocclusions in the vertical, transverse, sagittal planes with deleterious habits in pediatric patients. Methods A cross-sectional analytical study was carried out on 155 children aged 6–12 years attended at the clinic of the School of Dentistry of Universidad Nacional Mayor de San Marcos in 2017. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…However, in this study, a statistically significant relationship with unilateral posterior cross-bites was also obtained. A different contribution is also made by the study of Rodriguez-Olivos et al [ 26 ] in 2022, who found that 91.7% of the children with atypical swallowing presented an edge-to-edge bite.…”
Section: Discussionmentioning
confidence: 99%
“…However, in this study, a statistically significant relationship with unilateral posterior cross-bites was also obtained. A different contribution is also made by the study of Rodriguez-Olivos et al [ 26 ] in 2022, who found that 91.7% of the children with atypical swallowing presented an edge-to-edge bite.…”
Section: Discussionmentioning
confidence: 99%
“…Deleterious oral habits: In mixed dentition, early identification and intervention should be performed for all kinds of bad oral habits, including mouth breathing, atypical swallowing, tongue thrusting, functional mandibular advancement, NNS (thumb, finger, cheek, or a similarly shaped object), lip biting, soft diet, bottle-feeding incompetent lip closure, unilateral chewing habits, etc. 98 , 130 – 132 Cooperating with early orthodontic treatment and actively carrying out functional training of maxillofacial muscles should be conducted. 133 – 138 Orofacial myofunctional therapy (OMT) targets oral and oropharyngeal structures, aiming to improve muscle tone, endurance, and coordinated movements in the pharynx and surrounding areas.…”
Section: Clinical Practice Of Early Orthodontic Treatment In Differen...mentioning
confidence: 99%
“…Breastfeeding is defined as one of the foundations of health promotion and the prevention of many diseases and is one of the pillars of correct maxillofacial growth because it favors proper lip sealing, jaw function and the position of the tongue against the palate [43]. Indeed, breastfeeding forces the child to actively extract milk from the mother's breast through the synergistic action of the tongue and facial muscles [7,[44][45][46][47][48]. In opposition, bottle feeding requires less effort to drain the milk, so it does not stimulate the functional matrix and favors the development of malocclusions such as a posterior crossbite, anterior open bite, increased protrusion and a class II molar and canine relationship.…”
Section: Breast-feeding Vs Bottle-feedingmentioning
confidence: 99%
“…The effect of NNSH depends on the nature, onset and duration of the habit. Sucking behaviors are physiological habits in newborns that stimulate the orofacial muscles and contribute to normal growth; however, the persistence of non-nutritive sucking habits can lead to long-term problems and create defects in the stomatognathic system [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%